A silicone scar gel and a method of making the same

CN122954723APending Publication Date: 2026-10-23YINGSHENGDA MEDICAL TECHNOLOGY (JIANGSU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611377327.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

部分方案通过添加保湿剂、植物提取物或药物活性成分增强功效,但该类成分与硅酮基质的相容性普遍不佳,长期贮存过程中易发生迁移、析出或分层,导致产品均一性与稳定性下降,且活性成分难以在皮肤表面持续滞留

Benefits of technology

[0024]1、本发明采用分两阶段滴加单体的接枝聚合方式,通过调控各阶段单体配比与滴加进程,实现了酸酐基团、苯硼酸基团及羟基基团沿接枝链的梯度分布;第一阶段构建的富酸酐接枝层可与聚硅氧烷主链形成稳定的键合体系,有效降低接枝反应空间位阻,提升接枝效率,减少均聚物副产物生成,提高产物纯度与批次重现性。第二阶段构建的功能化外层可使苯硼酸、羟基等活性基团充分外露,避免基团被包埋,保证功能位点的有效作用效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the technical field of medical materials, in particular to a silicone scar gel and a preparation method thereof, wherein the graft copolymer is obtained by the following steps: dissolving vinyl branched polydimethylsiloxane in an organic solvent, removing oxygen by nitrogen, and then adding a monomer mixture containing an initiator in two stages to carry out graft polymerization; and the reaction solution is purified and dried to obtain the graft copolymer; then the graft copolymer is uniformly mixed with volatile polysiloxane, polysiloxane oil, oil-soluble antioxidant and antiseptic and bactericidal agent, and the mixture is filled and sealed after defoaming to obtain the finished product. By constructing the graft structure with gradient distribution of functional groups, the compatibility of the functional components and the silicone matrix is improved, the precipitation risk is reduced, the product has excellent film-forming performance, skin hydration and biocompatibility, and has good storage stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical materials technology, and in particular to a silicone scar gel and its preparation method. Background Technology

[0002] During the skin wound healing process, excessive proliferation of fibroblasts and abnormal deposition of collagen fibers easily lead to the formation of pathological scar tissues such as hypertrophic scars and keloids. These not only affect the patient's appearance but are also often accompanied by itching, stinging, and limited local function, making them a common clinical problem in dermatology and plastic surgery. Currently, scar intervention methods include various approaches such as pressure therapy, corticosteroid injections, laser ablation, and topical preparations. Among these, topical silicone preparations are widely recognized as the first-line treatment for early scar prevention and mild scar treatment due to their non-invasive nature, ease of use, and high patient compliance.

[0003] Traditional silicone scar gels primarily use linear polydimethylsiloxanes and volatile siloxanes as their base. They work by forming a continuous, semi-closed siloxane film on the skin surface, maintaining stratum corneum hydration and regulating the water metabolism and microenvironment of scar tissue, thereby softening and smoothing scars. However, conventional silicone bases only provide physical hydration, offering limited functionality and having limited effectiveness against actively proliferating pathological scars, thus failing to meet clinical needs.

[0004] To enhance the scar-improving effects of silicone formulations, existing technologies attempt to introduce various functional ingredients into the matrix or chemically modify the siloxane backbone. Some approaches enhance efficacy by adding moisturizers, plant extracts, or pharmaceutical active ingredients; however, these ingredients generally have poor compatibility with the silicone matrix, easily migrating, precipitating, or delaminating during long-term storage, leading to decreased product uniformity and stability, and making it difficult for active ingredients to remain on the skin surface. Another approach involves introducing functional groups into polysiloxane molecules through graft polymerization; however, existing grafting processes mostly employ one-step polymerization, resulting in poor controllability of the functional group distribution on the molecular chain, easily leading to group accumulation and the embedding of active sites. Furthermore, the reaction process produces numerous homopolymer byproducts, and the product purification process is cumbersome, hindering product performance stability and large-scale application.

[0005] In summary, current silicone scar gels still have shortcomings in terms of matrix structure regulation, functional component compatibility, and usage stability. There is an urgent need to develop a new type of silicone scar gel that can balance good skin adhesion, stable efficacy release, and excellent storage performance. Summary of the Invention

[0006] To address the problems mentioned in the background section, this invention provides a silicone scar gel and its preparation method.

[0007] To achieve the above objectives, the present invention adopts the following technical solution:

[0008] A method for preparing a silicone scar gel, the method comprising two stages: preparation of a graft copolymer and gel compounding and molding, the specific steps of which are as follows:

[0009] S1. Preparation of graft copolymer: Vinyl branched polydimethylsiloxane was dissolved in an organic solvent, and nitrogen gas was introduced to remove oxygen. The nitrogen flow rate was controlled at 15-25 mL / min, and the bubbling deoxygenation time was 25-35 min. After deoxygenation, the temperature was raised to the reaction temperature and kept constant for 5-15 min. Nitrogen protection and stirring speed of 180-220 r / min were maintained throughout the reaction. The monomer mixture containing the initiator was added dropwise in two stages to carry out the polymerization reaction. After the addition was completed, the reaction was kept at the temperature to obtain the reaction solution. The reaction solution was purified and dried to obtain the graft copolymer.

[0010] The monomer mixture consists of methacrylic anhydride, 4-vinylphenylboronic acid, and hydroxyethyl methacrylate.

[0011] Further, in step S1, the reaction temperature is 69-71℃; the total mass ratio of the monomers in the two stages is 1:(1.8-2.2); the vinyl content of the vinyl-branched polydimethylsiloxane is 0.6-1.0wt%, and the kinematic viscosity is 400-600cSt; the mass ratio of vinyl-branched polydimethylsiloxane to organic solvent is 1:2.5-3.5.

[0012] Furthermore, in the first-stage monomer mixture, the mass ratio of methacrylic anhydride, 4-vinylphenylboronic acid and hydroxyethyl methacrylate is (4.8-5.5):1:(3.2-3.8).

[0013] Furthermore, in the second-stage monomer mixture, the mass ratio of methacrylic anhydride, 4-vinylphenylboronic acid, and hydroxyethyl methacrylate is 1:(2.6-3.2):(4.8-5.4).

[0014] Furthermore, the dropping rate of the monomer mixture in the first stage is 0.07-0.09 mL / min, the dropping time is 1.8-2.2 h, and the reaction is kept at the temperature for 2.5-3.5 h after the dropping is completed.

[0015] Furthermore, the dropping rate of the monomer mixture in the second stage was 0.09-0.11 mL / min, the dropping time was 2.3-2.7 h, and the reaction was kept at the temperature for 3.5-4.5 h after the dropping was completed.

[0016] Furthermore, the initiator is an azo radical initiator, selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and azobisisovalerate; the amount of initiator used is 1.0-1.2 wt% of the total mass of the monomers in the corresponding stage.

[0017] Further, the purification and drying in step S1 specifically involves: removing the solvent and residual monomer by vacuum distillation of the reaction solution at 50-60℃ and -0.08 to -0.09 MPa to obtain a crude product; dissolving the crude product in an ether solvent, then adding 8-12 times its volume of a lower alcohol precipitant dropwise under stirring to precipitate the product; allowing it to stand and separate into layers, then discarding the supernatant; repeating the dissolution-precipitation operation 2-4 times; and finally vacuum drying to constant weight at 55-65℃ and -0.08 to -0.10 MPa.

[0018] The ether solvent is selected from one or more of tetrahydrofuran and 2-methyltetrahydrofuran; the lower alcohol precipitant is selected from one or more of anhydrous methanol, anhydrous ethanol, and isopropanol.

[0019] Furthermore, the organic solvent is selected from one or more of butyl acetate, ethyl acetate, and propyl acetate; the organic solvent is dried by molecular sieve treatment and has a water content of not more than 100 ppm.

[0020] S2. Gel compounding and molding: The above graft copolymer is mixed evenly with volatile polysiloxane, polysiloxane oil, oil-soluble antioxidant, and preservative and bactericide. First, the mixture is stirred at a speed of 220-280 r / min for 15-25 min until the system is homogeneous and free of lumps. Then, the speed is reduced to 130-170 r / min and stirring is continued for 12-18 min. Subsequently, degassing treatment is performed. During degassing, the vacuum degree is controlled at -0.07 to -0.08 MPa, and the mixture is stirred at a speed of 80-120 r / min for 10-20 min. After degassing, the mixture is filled and sealed in a Class 10,000 clean environment to obtain silicone scar gel.

[0021] According to another aspect of the present invention, a silicone scar gel prepared by the above preparation method is provided, wherein, by mass parts, the silicone scar gel comprises 55-65 parts of graft copolymer, 28-36 parts of volatile polysiloxane, 5-8 parts of polysiloxane oil, 0.3-0.7 parts of oil-soluble antioxidant, and 0.8-1.2 parts of preservative and bactericide.

[0022] The volatile polysiloxane is selected from one or more of cyclopentadimethylsiloxane, cyclotetradimethylsiloxane, and cyclohexadimethylsiloxane; the polysiloxane oil is selected from one or more of dimethyl silicone oil and phenylmethyl silicone oil with a kinematic viscosity of 300-400 cSt; the oil-soluble antioxidant is selected from one or more of tocopheryl acetate, vitamin E succinate, and ascorbic acid tetraisopalmitate; and the preservative and bactericide is selected from one or more of phenoxyethanol, ethylhexylglycerin, and chlorphenesin.

[0023] The beneficial effects of this invention are:

[0024] 1. This invention employs a two-stage dropwise monomer grafting polymerization method. By controlling the monomer ratio and dropwise addition process at each stage, a gradient distribution of anhydride groups, phenylboronic acid groups, and hydroxyl groups along the graft chain is achieved. The anhydride-rich graft layer constructed in the first stage can form a stable bonding system with the polysiloxane backbone, effectively reducing steric hindrance in the grafting reaction, improving grafting efficiency, reducing the formation of homopolymer byproducts, and improving product purity and batch reproducibility. The functionalized outer layer constructed in the second stage allows active groups such as phenylboronic acid and hydroxyl groups to be fully exposed, avoiding group embedding and ensuring the effective functioning efficiency of the functional sites.

[0025] 2. The graft copolymer obtained by this invention has polydimethylsiloxane as the main chain backbone and is grafted with polar functional side chains. It has good compatibility with volatile polysiloxane and polysiloxane oil components, and can significantly improve the dispersion uniformity and storage stability of oil-soluble antioxidants and preservatives in silicone matrix, inhibit component migration, precipitation and stratification during long-term storage, and improve the shelf stability of products.

[0026] 3. The silicone scar gel of the present invention combines the physical barrier function of silicone matrix with the regulatory effect of functional components. The polysiloxane component can form a uniform and breathable continuous film on the skin surface to maintain the normal hydration of the stratum corneum. The functional groups can synergistically regulate the local microenvironment of the scar and assist in the repair of the skin barrier. Compared with conventional silicone preparations that only have physical hydration effect, the intervention effect on pathological scars is more prominent.

[0027] 4. The preparation process of the present invention has mild reaction conditions, strong parameter controllability, simple purification process, no need for special production equipment, easy to realize industrial scale-up production, and the obtained product has stable performance and good quality uniformity. Detailed Implementation

[0028] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0029] Example 1

[0030] The preparation method of silicone scar gel in this embodiment includes the following steps:

[0031] S1. Preparation of graft copolymers:

[0032] Weigh 10.00g of vinyl-branched polydimethylsiloxane (vinyl content 0.8wt%, kinematic viscosity 500cSt) and add it to the reaction vessel. Add 30.00g of dry butyl acetate (moisture content ≤100ppm), start stirring, and set the speed to 200r / min. Purge with 20mL / min of high-purity nitrogen to remove oxygen for 30min. After deoxygenation, raise the temperature to 70℃ and keep it constant for 10min.

[0033] Prepare the first-stage monomer mixture: total mass 1.00 g, including 0.52 g methacrylic anhydride, 0.10 g 4-vinylphenylboronic acid, and 0.38 g hydroxyethyl methacrylate (mass ratio 5.2:1:3.8), and add 0.011 g azobisisobutyronitrile (1.1 wt% of monomer mass), dissolved in 10.00 g butyl acetate. Maintain the reaction system at 70 °C, under nitrogen protection and stirring, and add the monomer dropwise at a rate of 0.08 mL / min for 2.0 h; after the addition is complete, maintain the reaction temperature for 3.0 h.

[0034] Prepare the second-stage monomer mixture: 2.00 g total mass, including 0.22 g methacrylic anhydride, 0.64 g 4-vinylphenylboronic acid, and 1.14 g hydroxyethyl methacrylate (mass ratio 1:2.9:5.1). Add 0.022 g azobisisobutyronitrile (1.1 wt% of monomer mass) dissolved in 15.00 g butyl acetate. Keeping the reaction conditions constant, add the monomer dropwise at a rate of 0.10 mL / min for 2.5 h. After the addition is complete, maintain the temperature for 4.0 h to obtain the reaction solution.

[0035] The reaction solution was subjected to vacuum distillation at 55℃ and -0.085MPa to remove the solvent and residual monomers, yielding a crude product. The crude product was fully dissolved in tetrahydrofuran and then added dropwise to 10 times its volume of anhydrous methanol with stirring to precipitate the product. After standing and separating the layers, the supernatant was discarded. The dissolution-precipitation operation was repeated 3 times. Finally, the product was vacuum dried at 60℃ and -0.09MPa to constant weight to obtain the graft copolymer.

[0036] S2, Gel compounding molding:

[0037] Weigh out the following components by weight: 60.0 parts of the above graft copolymer, 32.0 parts of cyclopentasiloxane, 6.5 parts of dimethyl silicone oil (kinematic viscosity 350 cSt), 0.5 parts of tocopheryl acetate, and 1.0 part of phenoxyethanol. Add the graft copolymer, cyclopentasiloxane, and dimethyl silicone oil to a sealed stirred tank and stir at 250 rpm for 20 min at room temperature until the system is homogeneous. Reduce the stirring speed to 150 rpm, add tocopheryl acetate and phenoxyethanol sequentially, and continue stirring for 15 min. Control the vacuum degree to -0.075 MPa and stir at 100 rpm for 15 min to degas. After degassing, fill and seal in a Class 10,000 cleanroom environment to obtain silicone scar gel.

[0038] Example 2

[0039] The preparation method of silicone scar gel in this embodiment is basically the same as that in Example 1, except that:

[0040] In step S1, the reaction temperature is 69℃; the total mass of monomers in the first stage is 1.00g, the total mass of monomers in the second stage is 1.80g, and the mass ratio of monomers in the two stages is 1:1.8; the amount of azobisisobutyronitrile used is 1.0wt% of the total mass of monomers in the corresponding stage.

[0041] During purification and drying, the vacuum distillation temperature is 50℃ and the vacuum degree is -0.08MPa; the dissolution-precipitation process is repeated twice, and the vacuum drying temperature is 55℃ and the vacuum degree is -0.08MPa.

[0042] Example 3

[0043] The preparation method of silicone scar gel in this embodiment is basically the same as that in Example 1, except that:

[0044] In step S1, the reaction temperature is 71℃; the total mass of monomers in the first stage is 1.00g, the total mass of monomers in the second stage is 2.20g, and the total mass ratio of monomers in the two stages is 1:2.2; the amount of azobisisobutyronitrile used is 1.2wt% of the total mass of monomers in the corresponding stage.

[0045] During purification and drying, the vacuum distillation temperature was 60℃ and the vacuum degree was -0.09MPa; the dissolution-precipitation process was repeated 4 times, and the vacuum drying temperature was 65℃ and the vacuum degree was -0.10MPa.

[0046] Example 4

[0047] The preparation method of silicone scar gel in this embodiment is basically the same as that in Example 1, except that:

[0048] In step S1, the mass ratio of methacrylic anhydride, 4-vinylphenylboronic acid and hydroxyethyl methacrylate in the first-stage monomer mixture is 5.5:1:3.2; the dropping rate of the first-stage monomer mixture is 0.07 mL / min, the dropping time is 2.2 h, and the reaction is kept at the temperature for 2.5 h after the dropping is completed.

[0049] Example 5

[0050] The preparation method of silicone scar gel in this embodiment is basically the same as that in Example 1, except that:

[0051] In step S1, the mass ratio of methacrylic anhydride, 4-vinylphenylboronic acid and hydroxyethyl methacrylate in the second-stage monomer mixture is 1:2.6:5.4; the dropping rate of the second-stage monomer mixture is 0.11 mL / min, the dropping time is 2.3 h, and the reaction is kept at the temperature for 4.5 h after the dropping is completed.

[0052] Example 6

[0053] The preparation method of silicone scar gel in this embodiment is basically the same as that in Example 1, except that:

[0054] In step S2, the following components are weighed by mass: 55.0 parts of graft copolymer, 36.0 parts of cyclopentamethoxysiloxane, 7.5 parts of phenylmethyl silicone oil (kinematic viscosity 350 cSt), 0.7 parts of tocopheryl acetate, and 0.8 parts of phenoxyethanol.

[0055] Example 7

[0056] The preparation method of silicone scar gel in this embodiment is basically the same as that in Example 1, except that:

[0057] In step S2, the following components are weighed by mass: 65.0 parts of graft copolymer, 28.0 parts of cyclotetrameric dimethylsiloxane, 5.5 parts of dimethyl silicone oil (kinematic viscosity 350 cSt), 0.3 parts of vitamin E succinate, and 1.2 parts of phenoxyethanol.

[0058] Comparative Example 1

[0059] The difference between this comparative example and Example 1 is that the graft polymerization is carried out in one step: the monomers and initiators from the two stages are combined and prepared into a single mixture, which is then added dropwise at a uniform rate over a period of 4.5 hours. After the addition is complete, the reaction is maintained at the temperature for 4.0 hours. All other process parameters and operations are the same as in Example 1.

[0060] Comparative Example 2

[0061] The difference between this comparative example and Example 1 is that 4-vinylphenylboronic acid is not added to the monomer mixture, the total mass of monomers in both stages remains unchanged, and the corresponding mass is made up by methacrylic anhydride and hydroxyethyl methacrylate in the original ratio; the remaining process parameters and operations are the same as in Example 1.

[0062] Comparative Example 3

[0063] The difference between this comparative example and Example 1 is that methacrylic anhydride is not added to the monomer mixture, the total mass of monomers in both stages remains unchanged, and the corresponding mass is made up by 4-vinylphenylboronic acid and hydroxyethyl methacrylate in the original ratio; the remaining process parameters and operations are the same as in Example 1.

[0064] Comparative Example 4

[0065] The difference between this comparative example and Example 1 is that, in the gel compounding step, the self-made graft copolymer is not used, and an equal mass of vinyl-branched polydimethylsiloxane is used directly to replace the graft copolymer for mixing; the remaining process parameters and operations are the same as in Example 1.

[0066] Comparative Example 5

[0067] The difference between this comparative example and Example 1 is that the monomer composition in the two stages is interchanged: in the first stage, the monomer mixture with the original proportion of the second stage is added dropwise, and in the second stage, the monomer mixture with the original proportion of the first stage is added dropwise, while the total mass of monomers in both stages remains unchanged; all other process parameters and operations are the same as in Example 1.

[0068] The silicone scar gels prepared in Examples 1 to 7 were used as experimental group samples, numbered S1 to S7 in sequence. The samples prepared in Comparative Examples 1 to 5 were used as control group samples, numbered D1 to D5 in sequence, for a total of 12 groups of samples. Each group of samples was prepared in parallel in 3 copies. All performance tests were set up in 3 parallel replicates, and the results were taken as average values.

[0069] First, accelerated storage stability was investigated, including three tests: room temperature incubation, thermal cycling, and centrifugal stability. In the room temperature incubation test, each group of samples was sealed in clean colorimetric tubes and placed in a constant temperature environment of 25℃ for 30 consecutive days. The appearance of the samples was visually observed on days 0, 7, 15, and 30, and the presence of stratification, turbidity, oil precipitation, clumping, or color changes was recorded. In the thermal cycling test, each group of sealed samples was first placed in a constant temperature incubator at 40℃ for 12 hours, then transferred to a low temperature environment of -5℃ for 12 hours. This constituted one cycle, which was repeated 10 times before returning to room temperature. The uniformity of the sample appearance and changes in state were observed. In the centrifugal stability test, 5g of each sample was weighed into a 10mL centrifuge tube and centrifuged at 3000 rpm for 30 minutes. After centrifugation, the presence of precipitation at the bottom of the centrifuge tube and the presence of oil phase precipitation on the upper layer were observed to evaluate the storage stability of the system.

[0070] During the in vitro film-forming performance test, the ambient temperature was controlled at 25℃ and the relative humidity at 60%. A 400μm coating applicator was used to uniformly coat the gel sample onto the surface of a clean glass plate with a coating area of ​​5cm×5cm. Timing was started immediately after coating. The film-forming endpoint was defined as the formation of a continuous transparent film when the film surface was lightly touched with a finger without any stickiness or stringing. The film-forming time of each group of samples was recorded. After film formation, the samples were allowed to stand for another 2 hours to observe whether the film layer was uniform and smooth, and whether there were any defects such as cracks or edge shrinkage. Each group of samples was tested in parallel 3 times, and the average film-forming time was calculated.

[0071] The skin stratum corneum hydration rate test was conducted in a temperature- and humidity-controlled chamber, with the ambient temperature maintained at 25°C and the relative humidity at 50%. Six healthy subjects were recruited, and 12 test areas of 2cm × 2cm were marked on the inner forearm. No skincare products were applied to the test areas for 24 hours prior to the test. After the subjects sat quietly in the temperature- and humidity-controlled chamber for 30 minutes to acclimatize, the initial stratum corneum hydration rate of each test area was measured using a skin moisture meter. Subsequently, a 2mg / cm² skin moisturizing agent was evenly applied to each test area. 2 The hydration rate of the stratum corneum in the corresponding area was measured again at 2 hours, 6 hours and 12 hours after application of the gel sample, and the hydration rate increase value was calculated according to formula (1):

[0072] W=W t -W0(1);

[0073] In the formula: W is the increase in stratum corneum hydration rate; W t Wt represents the stratum corneum hydration rate at time t after application; W0 represents the initial stratum corneum hydration rate. Each sample group corresponds to one test area, and the final result is the average of the test data from all subjects.

[0074] In the component compatibility and precipitation test, 10g of each sample was weighed, sealed, and placed in a 40℃ constant temperature incubator for 15 days. After being taken out, it was centrifuged at 3000r / min for 20 minutes, and the supernatant was carefully collected. Using a blank silicone matrix without added functional components as a reference, the absorbance of the precipitate was measured by a UV-Vis spectrophotometer at the characteristic absorption wavelength of the active components. The mass of the precipitate was calculated by using a pre-drawn standard curve, and then the precipitation rate of the active components was calculated. The precipitation rate of the active components was calculated according to formula (2):

[0075] R = (m1 / m0) × 100% (2);

[0076] In the formula: R is the precipitation rate of the active component; m1 is the mass of the active component in the precipitate; m0 is the theoretical total mass of the active component in 10g of sample. This formula is used to evaluate the compatibility of each functional component with the silicone matrix, with each sample tested in triplicate.

[0077] In vitro fibroblast compatibility was evaluated using NIH / 3T3 mouse embryonic fibroblasts. Sample extracts were prepared by adding each group of gel samples to serum-free DMEM medium at a ratio of 1.0 g / mL and extracting at 37°C for 24 hours. After extraction, the samples were filtered through a 0.22 μm filter for sterilization to obtain the extracts for each group. Fibroblasts in the logarithmic growth phase were then cultured at a concentration of 5 × 10⁻⁶ cells / mL. 3 Cells were seeded at a density of 100 μL / well in 96-well culture plates, and 100 μL of complete culture medium was added to each well. The plates were then incubated at 37°C and 5% CO2 for 24 hours until the cells were fully adhered. The original culture medium in the wells was discarded, and 100 μL of complete culture medium containing different sample extracts was added to each well. A blank culture medium control group was also set up. Each group had 6 replicates. After culturing for 24 hours and 48 hours, 10 μL of LCK-8 reagent was added to each well, and the plates were incubated for another 2 hours. The absorbance at 450 nm was measured using a microplate reader, and the relative cell proliferation rate was calculated according to formula (3).

[0078] P=(A s / A c )×100%(3;

[0079] In the formula: P is the relative cell proliferation rate; A s A represents the absorbance value corresponding to the experimental group sample. c The absorbance value corresponds to the blank culture medium control group. This value is used to evaluate the cell biocompatibility of the samples. The entire experiment was repeated three times.

[0080] The results are shown in Table 1-5:

[0081] Table 1. Results of accelerated storage stability test

[0082]

[0083] Note: √ indicates that the appearance is uniform and transparent, without layering, oil separation, turbidity or clumping; △ indicates slight oil separation or slight turbidity, without obvious layering; × indicates obvious layering, oil separation or clumping.

[0084] Table 2. Results of in vitro film-forming performance test (n=3)

[0085]

[0086] Table 3. Results of the test on the increase in skin stratum corneum hydration rate (n=6)

[0087]

[0088] Table 4. Results of activity group analysis (placed at 40℃ for 15 days, n=3)

[0089]

[0090] Table 5. Results of relative proliferation rate assay for NIH / 3T3 cells (n=3)

[0091] As shown in Table 1, after 30 days of standing at room temperature, 10 cycles of hot and cold cycling, and centrifugation at 3000 r / min for 30 min, the samples of Examples 1-7 all maintained a uniform and transparent appearance, without layering, oil separation, turbidity, or clumping, indicating that the silicone scar gel prepared by this invention has excellent storage stability. This invention employs a two-stage stepwise graft polymerization process to construct a copolymer structure with functional groups distributed along the graft chain gradient. The anhydride groups enriched in the inner layer form a stable bonding system with the polydimethylsiloxane backbone, reducing the steric hindrance of the grafting reaction and minimizing the formation of homopolymer byproducts. The polar functional groups in the outer layer can regulate the interfacial compatibility of the system. Combined with multiple dissolution-precipitation purification steps to remove residual monomers and free homopolymers, the phase separation tendency of the system is effectively suppressed, thereby improving the storage stability of the product. Comparative Example 1 uses a one-step polymerization method, resulting in a random distribution of functional groups and a higher homopolymer content, leading to decreased system compatibility. Comparative Examples 2 and 3 lack 4-vinylphenylboronic acid and methacrylic anhydride, respectively, disrupting the polarity and spatial structure of the grafted chains and weakening interfacial compatibility. Comparative Example 4 does not use graft copolymers, resulting in a lack of compatible media between the functional components and the silicone matrix. Comparative Example 5 reverses the order of monomer feeding in the two stages, reversing the polarity gradient and embedding the functional groups. Therefore, all comparative examples exhibit varying degrees of oil separation, turbidity, or stratification, significantly reducing storage stability.

[0092] As shown in Table 2, the film-forming time for samples in Examples 1-7 was 3.2-3.6 min. The resulting films were uniform and transparent, without cracks or edge shrinkage defects, indicating that the silicone scar gel of this invention has a fast film-forming speed and excellent film quality. The gradient structure graft copolymer of this invention can reduce the cohesive energy of the gel system, improve the spreading fluidity during coating, and exhibit good compatibility among the components. There is no phase separation or shrinkage during film formation, thus enabling the rapid formation of a uniform and continuous film. Comparative Example 1, due to its non-uniform polymer structure, suffered from poor molecular arrangement regularity during film formation, resulting in prolonged film-forming time and slight haze. Comparative Example 4 exhibited poor system compatibility, leading to easy phase shrinkage and edge shrinkage defects during film formation. The remaining comparative examples showed varying degrees of decrease in film-forming speed and film uniformity due to defects in the graft structure or components.

[0093] As shown in Table 3, the stratum corneum hydration rate of the samples in Examples 1-7 increased by 19.5%-21.3% after 2 hours of application and remained at 13.5%-15.2% after 12 hours. The hydration effect is significant and long-lasting, indicating that the silicone scar gel of this invention has excellent skin moisturizing and hydration regulation capabilities. This invention, through second-stage outer layer functionalization grafting, enriches polar groups such as hydroxyl and phenylboronic acid at the graft chain ends. These groups can bind water molecules through hydrogen bonding, and combined with the sealing and water-retaining effect of the continuous film formed by the silicone matrix, achieves a dual hydration effect of physical sealing and polar hygroscopic absorption. Furthermore, the gradient structure ensures effective exposure of functional groups, fully leveraging the moisturizing effect. Comparative Example 1 showed poor film uniformity, resulting in a weakened sealing and water retention effect. Comparative Examples 2 and 3 lacked some polar functional groups, leading to a decrease in moisture absorption and retention capacity. Comparative Example 4 relied solely on the physical sealing effect of the silicone matrix, resulting in a weak hydration effect and rapid attenuation. In Comparative Example 5, the functional groups were embedded in the inner layer of the grafted chain, failing to effectively exert a moisturizing effect. Therefore, the stratum corneum hydration rate improvement values ​​of each comparative example were significantly lower than those of the examples.

[0094] As shown in Table 4, after being placed at 40℃ for 15 days, the precipitation rate of the active components in the samples of Examples 1-7 was only 0.62%-0.91%, far lower than that of the comparative examples, indicating that the functional components in the system of this invention have excellent compatibility with the silicone matrix. The graft copolymer of this invention has both a hydrophobic siloxane backbone and a polar functional side chain, which can act as an interfacial compatibilizer to enhance the interaction between the oil-soluble antioxidant, preservative and bactericide and the silicone matrix, limiting the migration and precipitation of functional components. At the same time, the purification step effectively removes free small molecule impurities, further reducing the risk of precipitation. Comparative Example 1 produced a large amount of homopolymer due to one-step polymerization, resulting in decreased system compatibility; Comparative Examples 2 and 3 had incomplete graft structures, weakening the anchoring and compatibility of functional components; Comparative Example 4 lacked the interfacial compatibility of the graft copolymer, making the functional components prone to migration; Comparative Example 5 had a reversed polar gradient and weak binding force with the matrix. Therefore, the precipitation rate of the active components in each comparative example was significantly increased.

[0095] As shown in Table 5, after the extracts of Examples 1-7 were applied to NIH / 3T3 cells, the relative cell proliferation rate remained above 95% at both 24h and 48h, with no significant cell inhibition, indicating that the silicone scar gel of the present invention has good biocompatibility. The present invention effectively removes residual monomers, initiators, and homopolymer byproducts through a multiple dissolution-precipitation purification process. Simultaneously, the functional components are stably dispersed in the system with low precipitation, resulting in low impurity content in the extract and no significant impact on the normal proliferation of fibroblasts. The comparative groups, due to high homopolymer residue and high levels of active group precipitates, had relatively higher impurity content in their extracts, leading to varying degrees of inhibition on fibroblast proliferation. Comparative Example 3, lacking anhydride groups, and Comparative Example 4, which did not use graft copolymers, showed the lowest cell proliferation rates, directly related to the high impurity content and high amount of precipitates in the system.

[0096] In summary, this invention constructs a siloxane graft copolymer with a gradient distribution of functional groups through a two-stage stepwise graft polymerization. Relying on the structural characteristics of stable inner layer bonding and exposed outer layer function, it effectively improves the interfacial compatibility between functional components and silicone matrix, reduces the risk of component elution, and endows the gel with excellent film-forming properties and skin hydration effects. Combined with purification processes to control impurity residues, the product exhibits significantly improved comprehensive performance in terms of storage stability, efficacy, and biocompatibility.

[0097] In the description of this specification, the reference to terms such as "embodiment," "various embodiments," etc., indicates that a specific feature, structure, material, or characteristic described in connection with that embodiment or preparation example is included in at least one embodiment of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments.

[0098] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a silicone scar gel, characterized in that, Includes the following steps: S1. Vinyl branched polydimethylsiloxane is dissolved in an organic solvent, nitrogen is introduced to remove oxygen, and the temperature is raised. A monomer mixture containing an initiator is added dropwise in two stages to carry out the polymerization reaction. After the addition is completed, the reaction is kept at the temperature to obtain a reaction solution. The reaction solution is purified and dried to obtain a graft copolymer. S2. The graft copolymer is mixed evenly with volatile polysiloxane, polysiloxane oil, oil-soluble antioxidant, and preservative and bactericide. After degassing, it is filled and sealed to obtain silicone scar gel. The monomer mixture consists of methacrylic anhydride, 4-vinylphenylboronic acid, and hydroxyethyl methacrylate.

2. The preparation method according to claim 1, characterized in that, In step S1, the reaction temperature is 69-71℃; the total mass ratio of the monomers in the two stages is 1:(1.8-2.2).

3. The preparation method according to claim 1, characterized in that, In step S1, the mass ratio of methacrylic anhydride, 4-vinylphenylboronic acid and hydroxyethyl methacrylate in the first-stage monomer mixture is (4.8-5.5):1:(3.2-3.8).

4. The preparation method according to claim 1, characterized in that, In step S1, the mass ratio of methacrylic anhydride, 4-vinylphenylboronic acid and hydroxyethyl methacrylate in the second-stage monomer mixture is 1:(2.6-3.2):(4.8-5.4).

5. The preparation method according to claim 1, characterized in that, In step S1, the dropping rate of the monomer mixture in the first stage is 0.07-0.09 mL / min, the dropping time is 1.8-2.2 h, and the reaction is kept at the temperature for 2.5-3.5 h after the dropping is completed.

6. The preparation method according to claim 1, characterized in that, In step S1, the dropping rate of the monomer mixture in the second stage is 0.09-0.11 mL / min, the dropping time is 2.3-2.7 h, and the reaction is kept at the temperature for 3.5-4.5 h after the dropping is completed.

7. The preparation method according to claim 1, characterized in that, In step S1, the initiator is an azo radical initiator, selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and azobisisovalerate; its amount is 1.0-1.2 wt% of the total mass of the monomers in the corresponding stage.

8. The preparation method according to claim 1, characterized in that, In step S1, the purification and drying process specifically involves: removing the solvent and residual monomers from the reaction solution by vacuum distillation to obtain the crude product; dissolving the crude product in an ether solvent, adding 8-12 times its volume of a lower alcohol precipitant to precipitate it, discarding the supernatant, and repeating the dissolution-precipitation operation 2-4 times; and then vacuum drying to constant weight at 55-65℃ and -0.08 to -0.10 MPa. The ether solvent is selected from one or more of tetrahydrofuran and 2-methyltetrahydrofuran; the lower alcohol precipitant is selected from one or more of anhydrous methanol, anhydrous ethanol, and isopropanol.

9. The preparation method according to claim 1, characterized in that, In step S1, the organic solvent is selected from one or more of butyl acetate, ethyl acetate, and propyl acetate.

10. A silicone scar gel, characterized in that, Prepared by the preparation method according to any one of claims 1-9; comprising, by mass parts, 55-65 parts of graft copolymer, 28-36 parts of volatile polysiloxane, 5-8 parts of polysiloxane oil, 0.3-0.7 parts of oil-soluble antioxidant, and 0.8-1.2 parts of preservative and bactericide; The volatile polysiloxane is selected from one or more of cyclopentadimethylsiloxane, cyclotetradimethylsiloxane, and cyclohexadimethylsiloxane; Oil-soluble antioxidants are selected from one or more of tocopheryl acetate, vitamin E succinate, and ascorbate tetraisopalmitate; The preservative and bactericide is selected from one or more of phenoxyethanol, ethylhexylglycerin, and chlorphenesin.